THE IMPLICATIONS OF CLIMATE CHANGE ON STAPLE CROPS PRODUCTION IN EKPOMA, EDO STATE, NIGERIA - ILENRE ABRAHAM EHIZOJIE (International Studies Journal)
This paper examined the implications of climate change on staple crops production in Ekpoma, Edo State, Nigeria. The paper identified the causes of climate change,the staple crop cultivated, the major evidence of climate change having implications on staple crops production, the implications of climate change on staple crops production, and  the several adaptation strategies that have been proposed and implemented to mitigate its implications on staple crops production. To achieve these objectives, the researcher used both primary and secondary research methods to collect the data used for the study. Four hundred (400) staple crop farmers which represent two-point five percent (2.5%) of the staple crops farmers’ population in the study area were considered. Consequent upon the above, four hundred questionnaires were administered across the study area.The data obtained were analysed using tables, graphs and, percentages. The results reveal the causes of climate change in Ekpoma, the staple crops produced in Ekpoma at present, the major evidence of climate change having implications on staple crops production in Ekpoma, the implications of climate change on staple crops production in Ekpoma, Nigeriaand the adaptation strategies that have been used to mitigate its implications on staple crops production.Arising from the above findings, the following recommendations are made which include: effective and regular training and retraining of staple crops farmers on the knowledge of climate change, climate change related- hazards, the place of staple crops in Ekpoma, climatic conditions should be monitored to help predict potential climate change related hazards and how to circumvent them, practicing climate-smart agriculture which includes incorporating climate-hazard resistant crops and improving cultural practices, sustainable practices to manage diseases without harming the environment. governments at all levelsshould as a matter of urgency promulgate laws on the granting of soft loans, climate change related-hazards and diseases resistant species of staple crops and other inputs to staple crops farmers annually to encourage them.This paper is therefore concluded by advising the governments at all levels to effect the recommendations made by the researcher.